SURFACE RUNOFF AND EROSION FROM AGROFORESTRY LAND USE TYPES - Naharuddin; Rukmi; R. Wulandari; A. K. Paloloang (Journal of Animal and Plant Sciences, 2018)
Various systems of land use have a different capability in its function as a hydrological parameter and erosion. Surface runoff and erosion depends on the type of land use applied. The objective of this research was to find out the rate of surface runoff and erosion from agroforestry land use types at Miu sub-watershed, Palu watershed, Central Sulawesi, Indonesia, 2016. The method used was the multislot divisor on a plot measured 22 m x 2 m with 3 repetitions in 3 types of land use with a slope of 25-40% (steep). The result showsed that the largest surface runoff amounted from non- agroforestry land use type (10-year-old pure cocoa) by 72.674 liters/ha, followed by teak tree- and cocoa based agroforestry system aged 10 years old amounting to 59.815 liters/ha and the smallest is Candlenut tree-and cocoa-based agroforestry system aged 10 years old by 45.983 liters/ha. The highest erosion was recorded from non-agroforestry land use type (10-year-old pure cocoa) by 4,125 grams/ha, followed by teak tree- and cocoa based agroforestry system aged 10 years old amounting to 2,749 grams/ha and candlenut- and cocoa-based agroforestry system aged 10 years old by 1,280 grams/ha. Candlenut- and cocoa-based agroforestry system aged 10 was more effective to manage surface runoff and erosion rate. the conditions of erosion far above the value of etol
Keywords: Surface runoff; erosion; watershed; land use; agroforestry.